2019
DOI: 10.3390/en12163195
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Petroleum Coke Soot as Energy Storage Material

Abstract: Anode active materials for lithium ion batteries (LIBs) were produced by using waste soot generated after combustion in a plant using petroleum coke as fuel. The soot collected from the boilers in the plant was graphitized through annealing, and this annealed soot was applied to anode active materials. After annealing at 2700 °C, the soot was converted into highly crystalline graphite with ring shapes approximately 100 nm in diameter. The lithium ion coin cells produced using graphitized soot showed high disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…To address this gap, this study characterizes the soot generated from naval ship diesel engines that only use MGO and examines its applicability as the active material for LIB anodes. Furthermore, previous studies required graphitization at 2000 C or higher temperatures to manifest excellent performance as an electrode material for LIBs, 6 but this study found that a much lower temperature of 1000 C was adequate. The results thus demonstrate the future potential of LIBs based on heat-treated soot collected from propulsion diesel engines for the guided missile frigate (FFG), the main battleship of the South Korean Navy (Fig.…”
Section: Introductionmentioning
confidence: 60%
“…To address this gap, this study characterizes the soot generated from naval ship diesel engines that only use MGO and examines its applicability as the active material for LIB anodes. Furthermore, previous studies required graphitization at 2000 C or higher temperatures to manifest excellent performance as an electrode material for LIBs, 6 but this study found that a much lower temperature of 1000 C was adequate. The results thus demonstrate the future potential of LIBs based on heat-treated soot collected from propulsion diesel engines for the guided missile frigate (FFG), the main battleship of the South Korean Navy (Fig.…”
Section: Introductionmentioning
confidence: 60%
“…Higher SO2 emissions can be avoided by mixing low sulfur coke into the coke aggregate or removing sulfur by increasing the calcination temperature of the coke and increasing the residence time in the coke. However, this will result in higher coke unsuitable for anode preparation due to the decrease in bulk density caused by increased sulfur content [6].…”
Section: Comparison Of Rotary Kiln and Vertical Shaft Kiln Technologymentioning
confidence: 99%
“…Calcined Petroleum Coke (CPC) is required as a quality standard for graphite electrode and anode paste products [1], needle-grade [2], TiO₂ pigments [3]. The current use of CPC is for the aluminum (70%) [4], titanium dioxide (10%) industry as well as the foundry [5], steel and electrode industries [6]. CPC is also required in in the food grade phosphate [7] and the calcium carbide industry [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, the world's energy and environmental problems have become more and more prominent, which makes it urgent to improve energy efficiency and develop sustainable energy techniques. Moving bed heat exchanger (MBHE), with the advantages of low cost, clean energy and wide particle size adaptation, is gradually applied in many high temperature waste heat recovery industries [1], such as slag [2], cement [3], coke [4] and concentrated solar power (CSP) [5]. For the MBHE, the granular flow inside is driven by the gravity, and the heat transfer is relatively lower [6] as compared with packed bed [7] or fluidized bed [8].…”
Section: Introductionmentioning
confidence: 99%